On Optimization Model for a Bank Loan Portfolio for a Local City Bank in India - Jha, P.C.; Aggarwal, Remica (Contemporary Research in Business, Management and Economics Vol. 7, 2024)
The following chapter is research on bank loan optimization and tries to optimize its portfolio using a standard mathematical programming approach. The main objective of this research is to devise a method that optimizes the funding of the bank division’s Loan portfolio.